4(x-3)=1(7x+28)+3

Simple and best practice solution for 4(x-3)=1(7x+28)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)=1(7x+28)+3 equation:


Simplifying
4(x + -3) = 1(7x + 28) + 3

Reorder the terms:
4(-3 + x) = 1(7x + 28) + 3
(-3 * 4 + x * 4) = 1(7x + 28) + 3
(-12 + 4x) = 1(7x + 28) + 3

Reorder the terms:
-12 + 4x = 1(28 + 7x) + 3
-12 + 4x = (28 * 1 + 7x * 1) + 3
-12 + 4x = (28 + 7x) + 3

Reorder the terms:
-12 + 4x = 28 + 3 + 7x

Combine like terms: 28 + 3 = 31
-12 + 4x = 31 + 7x

Solving
-12 + 4x = 31 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-12 + 4x + -7x = 31 + 7x + -7x

Combine like terms: 4x + -7x = -3x
-12 + -3x = 31 + 7x + -7x

Combine like terms: 7x + -7x = 0
-12 + -3x = 31 + 0
-12 + -3x = 31

Add '12' to each side of the equation.
-12 + 12 + -3x = 31 + 12

Combine like terms: -12 + 12 = 0
0 + -3x = 31 + 12
-3x = 31 + 12

Combine like terms: 31 + 12 = 43
-3x = 43

Divide each side by '-3'.
x = -14.33333333

Simplifying
x = -14.33333333

See similar equations:

| 5i-1=14Xi | | 9(x+4)-5=39-6x-8+15x | | -4(4x-3)-(6x+4)= | | a^2+ab+b^2=0 | | X-4-3x=-3x-3-1 | | -4(9a-b)+3(5a+2b)=0 | | 2x+4(2x-4)=-6 | | 2x+(-8)=-2 | | x^2+6x+5x+4+5=69 | | 107=-2n+5(1+6n) | | 7x-5-72=0 | | 2g+3(-4+5g)=1-g | | -4(3x+2)=(6x-6) | | 5i-1=14i | | 2t^2-9t+13=0 | | (-3)(2)(-5)= | | -3y+4=4y+8 | | 4x-3-x+5-9x= | | 30.98-40.00=c | | 3x+2=720 | | 16a-5b-(-6a-15b)-(-4b)=0 | | 4(x+4)=5(x-2) | | 2t-24=20 | | 196x^2-121=0 | | 0=x^4-4x^3+2x^2+x+4 | | -5.7y-3.6+8.2y+3.6= | | 8.7=18.8m-13.5 | | 104=-16t^2+72 | | 2(x-5)=3(x-8) | | -7-6x=11 | | 13a^2-19a=14 | | .4x+.25(137-x)=39.73 |

Equations solver categories